Analisis biaya kualitas untuk mengurangi risiko produk cacat kantong persembahan pada Toko Buku Pustaka Mulia Manado - Kountul, Thezza Sthevany Helena; Gerungai, Natalia Y. T.; Mintalangi, Syermi S. E. (Yayasan Widyantara Nawasena Raharja, 2024)
Quality cost refers to the expenditure incurred both to prevent quality shortages and to handle the results from low-quality production to defective products. This study aims to determine the management of quality costs to reduce the risk of defective products in the Toko Buku Pustaka Mulia Manado. The research method used in this study is qualitative descriptive. The results show that quality costs in 2022 will increase in 2023. The management of quality costs for offering bag products at the Toko Buku Pustaka Mulia Manado has succeeded in reducing the number of defective products before they reach consumers. However, the cost of controlling quality at the Toko Buku Pustaka Mulia Manado is not efficient because it is not in accordance with the quality cost standards based on applicable theories and principles.